Leveraging Social Media Platforms to Enhance Students' English Proficiency: A Comprehensive Analysis - Reza Abedi, Seyed; Elahi, Salomeh (Language, Technology, and Social Media, 2023)
This study aims to examine the use of social media as a medium to enhance students' understanding of English, while also exploring the challenges, particularly the distractions caused by entertainment content. The method used in this research is qualitative with a literature review approach, analyzing various relevant literature, scholarly articles, and previous studies to investigate the impact of social media on English learning. The results show that social media platforms such as YouTube, TikTok, and Instagram provide wide access to educational content that helps students improve their English skills, including listening, speaking, grammar, and vocabulary. However, social media also presents a significant distraction risk, where students tend to be diverted to entertainment content rather than learning. This phenomenon is explained through various theories, such as Social Learning Theory, Cognitive Load, and Self-Regulated Learning. The study concludes that while social media holds great potential in supporting English learning, more directed strategies are needed to manage its use to maximize benefits and reduce the risk of distraction. Utilizing distraction control features, time management, and developing students' self-regulation skills are identified as key factors in enhancing the effectiveness of learning through social media.